Social Skills Training: Evaluating its Effectiveness for Students with Learning Disabilities, Emotional, and Behavioral Disorders - Campbell, Gregory (Journal of the American Academy of Special Education Professionals, 2008)
The purpose of this review is to describe important criteria used to evaluate the effectiveness of Social Skills Training Programs. The analysis defines social skills, discusses causes and effects of social skill deficits, and examines the research establishing criteria described by teachers, administrators, and students. The paper concludes with how these variables interact to affect the students’ response to intervention programs.